2002
DOI: 10.1002/ijc.10555
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of graft‐versus‐tumor responses in melanoma patients after allogeneic peripheral blood stem cell transplantation

Abstract: It has been shown that after allogeneic peripheral blood stem cell transplantation (PBSCT), donor T cells can induce potent graft-versus-tumor (GVT) effects in hematologic malignancies and possibly solid tumors such as renal cell carcinoma. Two patients (27 and 30 years old) with metastatic melanoma received allogeneic PBSCT from an HLA-identical sibling donor after reduced conditioning with fludarabine, carmustine and melphalan. One patient showed a delayed mixed response with complete regression of lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For example, approaches attempting to deplete the entire compartment or major subsets of T cells in the donor inoculum have not only led to an increase in the incidence of leukemic relapse, but also resulted in an increase in graft failure and opportunistic infections (20, 21). In recent years, we and others have demonstrated that CDR3-size spectratyping of the TCR Vβ chain can be utilized to differentiate alloreactive from uniquely tumor-reactive T cells, opening the door for potential tailoring of the donor inoculum to recipient’s malignancy (13, 22, 23). In other words, donor T cells could be selected for their specific tumor-reactivity, or depleted if confirmed to be uniquely alloreactive, in order to impart maximum benefit with reduction/elimination of deleterious side effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, approaches attempting to deplete the entire compartment or major subsets of T cells in the donor inoculum have not only led to an increase in the incidence of leukemic relapse, but also resulted in an increase in graft failure and opportunistic infections (20, 21). In recent years, we and others have demonstrated that CDR3-size spectratyping of the TCR Vβ chain can be utilized to differentiate alloreactive from uniquely tumor-reactive T cells, opening the door for potential tailoring of the donor inoculum to recipient’s malignancy (13, 22, 23). In other words, donor T cells could be selected for their specific tumor-reactivity, or depleted if confirmed to be uniquely alloreactive, in order to impart maximum benefit with reduction/elimination of deleterious side effects.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major challenges with HSC transplants is failure to engraft, which is mediated by donor T cells as a result of graft-versus-host disease (GVHD). Graft-versus-tumor effect of allogeneic HSC transplants may be a result of an immune reaction between donor cytotoxic T cells and patient's malignant cells [69]. MSCs are known to interact with HSCs and immune cells, and represent potential cellular therapy to enhance allogeneic hematopoietic engraftment and prevent GVHD [7072].…”
Section: Application Of Bone Marrow Mesenchymal Stem Cells In Hemamentioning
confidence: 99%
“…To date, peptide vaccination has resulted in a limited or marginal efficacy [19] while adoptive T lymphocyte infusion including Ag-specific CTL clones or TILs, especially after a lymphodepleted conditioning regimen, demonstrated promising results [20][21][22]. After allogeneic HSCT for patients with melanoma, there have been some reports indicating that CTLs against melanoma cells do exist and that these melanoma-reactive CTLs can be expanded in vitro [23,24]. These observations suggest that allogeneic HSCT after a nonmyeloablative conditioning regimen might be a promising therapeutic strategy for patients with refractory metastatic melanoma.…”
Section: Discussionmentioning
confidence: 44%